A dive into the human mind – From perception to emotions - Moreira , Paulo Cesar; Strini , Polyanne Junqueira Silva Andresen; Strini , Paulinne Junqueira Silva Andresen; Moreira , Stephânia de Oliveira Laudares; Moreira , Augusto Cesar Malta Laudares; Guimarães , Nilza Nascimento; Moura , Marcelo Cozac; Almeida , Nelson David Fernandes; Sousa , Rafael Dias de; Mesquita, Lívia Pereira de (Seven Editora, 2024)
Perception is the ability to associate sensory information with memory and cognition in order to form concepts about the world, ourselves and guide our behavior. From this concept, we understand that perception is a factor that depends on the senses, memory, cognition and behavior. Understanding the location of an object requires the coordination of sensory and motor information. Knowledge of auditory perception is less extensive than that of visual perception. This is due to the ease of studying visual perception and the difficulty in studying auditory perception, given that it doesn't exactly reflect the reality of sound from a physical point of view, i.e. there is a variation between the sound emitted by the sound source, the individual's perception and also the variation between different people. Attention is the process of focusing consciousness, concentrating mental processes on a single main task and leaving others in the background. This process is only possible through our ability to selectively sensitize a set of neurons in certain brain regions responsible for carrying out the main task, inhibiting the others. In order to understand the study of emotions and reason, we must start from the assumption that both are mental operations accompanied by an inner experience and are capable of guiding behavior and making the necessary physiological adjustments. Both reason and emotion are aspects of the same continuous organism, called the mind. Fear is a feeling initiated by various stimuli. The manifestations of fear are linked to preparing the body for an intense physical effort that could result in a fight or flight. Emotions are autonomic occurrences, however, they can be modulated by the use of reason, that is, by the action of the prefrontal cortex, which can alter behavior to favor the situation. Anger is the emotion that determines the behavior of aggression, whether it is defensive (related to fear) or offensive. Like fear, the region responsible for the initial trigger of aggression is the amygdala, which is connected to the hypothalamus. The study of pleasure relationships is extremely limited. Human beings have various forms of communication. They all involve two individuals: a sender of the signal (which must be standardized among the community) and a receiver of the signal. All languages have spoken communication and only a few have written communication. This characteristic stems from the fact that speech has a large innate neurological basis, while writing is a cultural construction whose learning depends on teaching. Writing is a means of communication restricted to a few languages and is the result of learning certain motor patterns of the hands in order to produce certain symbols that represent phonemes. This text seeks to delve into the human mind and highlight the main global and specific mechanisms that lead from perception to emotions in the light of current discussions on learning, teaching and the apprehension of knowledge. DOI:https://doi.org/10.56238/sevened2024.001-005